Desain Media Pembelajaran Interaktif Pengenalan Tata Surya Bagi Siswa-Siswi Sekolah Dasar - Ade Moussadecq; Muhammad Redintan Justin; Dika Tondo Widakdo (DEKAVE : Jurnal Desain Komunikasi Visual, 2024)
The use of interactive media can also increase student activity in learning and mastery of ideas, so that the learning experience received by students becomes more varied and not monotonous. The research method used is the Qualitative Descriptive method. The purpose of this study is to reveal events or facts, circumstances, phenomena, variables and conditions that occur during the research by explaining what actually happened. This study took a case study at SD Negeri 3 Rejosari, North Lampung Regency according to the needs of the research partners. The purpose of this study is to create an interactive learning media for students in introducing the solar system.